2020
DOI: 10.1007/s11869-020-00877-9
|View full text |Cite
|
Sign up to set email alerts
|

How is COVID-19 affecting environmental pollution in US cities? Evidence from asymmetric Fourier causality test

Abstract: This paper aims to examine the effects of the COVID-19 pandemic on PM 2.5 emissions in eight selected US cities with populations of more than 1 million. To this end, the study employs an asymmetric Fourier causality test for the period of January 15, 2020 to May 4, 2020. The outcomes indicate that positive shocks in COVID-19 deaths cause negative shocks in PM 2.5 emissions for New York, San Diego, and San Jose. Moreover, in terms of cases, positive shocks in COVID-19 cause negative shocks in PM 2.5 emissions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 25 publications
5
35
0
1
Order By: Relevance
“…They reported a significant drop in the NO x concentration level in the urban areas. Further, Pata ( 2020 ) studied the impact of COVID-19 pandemic on environmental pollution in eight different US cities and found that the ongoing pandemic decreased the PM2.5 emission in the US. Similarly, Sarfraz et al ( 2020 ) investigated the relationship between COVID-19 and NO2 concentration level in New York City and revealed that environmental quality significantly improved during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…They reported a significant drop in the NO x concentration level in the urban areas. Further, Pata ( 2020 ) studied the impact of COVID-19 pandemic on environmental pollution in eight different US cities and found that the ongoing pandemic decreased the PM2.5 emission in the US. Similarly, Sarfraz et al ( 2020 ) investigated the relationship between COVID-19 and NO2 concentration level in New York City and revealed that environmental quality significantly improved during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…This trend of increasing air quality was also found in Lima, Peru (Velásquez and Lara, 2020), Rio de Janeiro, Brazil ( Nakada and Urban, 2020 ) Almaty, Kazakhstan ( Kerimray et al, 2020 ), and in four Southern European cities (Nice, Rome, Valencia, and Turin; Sicard et al, 2020 ). Further, Pata (2020) studied the impact of COVID-19 pandemic on environmental pollution in eight different US cities and found that the ongoing pandemic decreased the PM 2.5 emission in the US. Similarly, Sarfraz et al (2020) investigated the relationship between COVID-19 and NO 2 concentration level in New York City and revealed that environmental quality significantly improved during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The usage of pesticides, soaps, detergents, single-use plastic etc. has increased many-fold in the past few months and is taking a heavy toll on the environment (Pata 2020 ; Zambrano-Monserrate et al 2020 ; Saadat et al 2020 ). Sanitization of roads, complexes and whole cities has been carried out in the past few months.…”
Section: Introductionmentioning
confidence: 99%